PENYULUHAN PENATALAKSANAAN NYERI REUMATOID ARTRITIS DI RUMAH PADA LANSIA - Hariati Hariati; Selamat Ginting; Nur Mala Sari (INSTITUT KESEHATAN DELI HUSADA, 2021)
Rheumatoid arthritis is one of the most common diseases affecting the elderly. This disease causes pain and decreased activity of the elderly on a daily basis. The problem that occurs in the elderly often experiences pain and loses the ability to carry out their activities. The alternative solution to the problem that can be done is by taking non-pharmacological actions. One very easy and inexpensive procedure is a warm compress. This action is very practical and can be done by everyone, including the elderly. This action is rarely done by the elderly when they are in pain. The service was carried out for the elderly as many as 42 people, namely counseling on rheumatoid arthritis, management of rheumatoid arthritis pain. The community service implementation team provides training on how to compress it to all elderly people who are in the work area of ​​the Medan Amplas Community Health Center Sevice. The team conducted a home visit to evaluate the community service program. Extension activities run smoothly. There were 10 elderly people who asked about counseling materials. It is important to do routine outreach activities to the elderly about other complaints they have to improve their health status.